Blended learning in improving students' mathematical critical thinking and mathematical communication abilitie - Nurdina, Tini; Yaniawati, Poppy; Al-Tamar, Jasem (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
The study aimed to determine the effect of the blended learning model on the achievement and improvement of students' mathematical communication in grade XI. The low ability of mathematical communication of high school students is a problem that requires teachers to be able to create and use a new approach in learning. This study uses a quantitative approach with quasi-experimental methods. There were two sample groups in this study, namely the experimental group of 28 students and the control group of 28 students. The sample was randomly selected from the class of SMA Pasundan 2 Cimahi students. The experimental group utilized blended learning model and the control group utilized an ordinary learning model. The instruments used in this study were descriptive and multiple choice tests for mathematical communication. The data obtained were then analyzed using tests for normality, homogeneity, and the difference between the two averages. N-gain data is used to determine the increase in students' mathematical communication. Based on the data analysis, it can be concluded that:  First, the achievement of students' mathematical communication skills who received blended learning was higher than students who received ordinary learning. And Second, the increase in the mathematical communication skills of students utilized blended learning is significantly higher than students utilized ordinary learning.